Cost-Effectiveness and Optimal Control of Hantavirus Transmission in Rodent Populations - Mahmoud Moustafa (Jambura Journal of Biomathematics (JJBM), 2026)
In this paper, we formulate and analyze a deterministic optimal control model for the transmission dynamics of hantavirus infection in rodent populations and identify economically efficient intervention strategies. The model incorporates three time-dependent controls: rodent harvesting, transmission reduction, and alien-oriented control. By applying Pontryagin’s Maximum Principle, we derive the Hamiltonian, the adjoint system, and explicit characterizations of the optimal controls, leading to the corresponding optimality system. Numerical solutions are obtained using a forward-backward sweep algorithm. Simulation results demonstrate that combined interventions can substantially reduce the infected rodent population; however, under limited resources, selecting a cost-effective policy is crucial. A health-economic evaluation based on the average and incremental cost-effectiveness ratios (ACER and ICER) shows that the joint implementation of harvesting and transmission reduction provides the most effective strategy among the alternatives considered. We further present a local normalized sensitivity analysis, highlighting the parameters that most strongly influence the predicted infections averted. These findings support the adoption of integrated, rodent-focused interventions for mitigating hantavirus transmission and offer quantitative guidance for informed public health decision-making.